DIPLOMASI KEBUDAYAAN INDONESIA TERHADAP TIONGKOK MELALUI KULINER ( GASTRODIPLOMACY) TAHUN 2016-2017 - Azizul Hakim; Faisyal Rani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This research is a political study that describes the culture of diplomacy (gastrodiplomacy) between Indonesia and China. This research focuses on how Indonesia's strategy in cultural diplomacy is through Indonesian cuisine this is qualitative research which used descriptive methods, and collecting datas from some resources like book, journals, official publications and relevant website. this paper used the neo-realism perspektif and nation-state from Paul R. Viotti and Mark V Kauppi. the object in this research is Indonesia as main actor in international relations The result of this research is that Indonesia has succeeded in organizing a culinary event in China, Indonesia has also succeeded in making a tempe factory. Then Indonesia has also set several policies and some Indonesian specialties that have become icons in the international world Keywords: Culture Diplomacy, Public Diplomacy, Gastrodiplomacy